Analiza sistemov za neposredno vbrizgavanje goriva v sodobne hitrotekoče dizelske motorje - Dolenc, Anton (Strojniški vestnik, 2001)
The development of the high-speed Diesel engines began in Europe 22 years ago. Since this time major technical problems have been encountered with the fuel system and its components. Different technical requirements have been met simultaneously: very high injection pressures, suitable pressure-to-time distribution, sophisticated injection timing control, reduced combustion noise and very stringent exhaust emission standards. General features, a comparison between some of the most advanced fuel-injection systems, and guidelines for the future are presented in the paper.
Keywords: motorji dizelski; motorji hitrohodni; vbrizgavanje goriva; vbrizgavanje direktno; dizelski motorji